Validity and reliability of an instrumented leg-extension machine for measuring isometric muscle strength of the knee extensors - Ruschel C.* (2015)
CONTEXT: Isometric muscle strength of knee extensors has been assessed for estimating performance, evaluating progress during physical training, and investigating the relationship between isometric and dynamic/functional performance.OBJECTIVE: To assess the validity and reliability of an adapted leg-extension machine for measuring isometric knee extensor force.DESIGN: Validity (concurrent approach) and reliability (test and test-retest approach) study.SETTING: University laboratory.PARTICIPANTS: 70 healthy men and women aged between 20 and 30 y (39 in the validity study and 31 in the reliability study).MAIN OUTCOME MEASURE: Intraclass correlation coefficient (ICC) values calculated for the maximum voluntary isometric torque of knee extensors at 30°, 60°, and 90°, measured with the prototype and with an isokinetic dynamometer (ICC2,1, validity study) and measured with the prototype in test and retest sessions, scheduled from 48 h to 72 h apart (ICC1,1, reliability study).RESULTS: In the validity analysis, the prototype showed good agreement for measurements at 30° (ICC2,1 = .75, SEM = 18.2 Nm) and excellent agreement for measurements at 60° (ICC2,1 = .93, SEM = 9.6 Nm) and at 90° (ICC2,1 = .94, SEM = 8.9 Nm). Regarding the reliability analysis, between-days' ICC1,1 were good to excellent, ranging from .88 to .93. Standard error of measurement and minimal detectable difference based on test-retest ranged from 11.7 Nm to 18.1 Nm and 32.5 Nm to 50.1 Nm, respectively, for the 3 analyzed knee angles.CONCLUSIONS: The analysis of validity and repeatability of the prototype for measuring isometric muscle strength has shown to be good or excellent, depending on the knee joint angle analyzed. The new instrument, which presents a relative low cost and easiness of transportation when compared with an isokinetic dynamometer, is valid and provides consistent data concerning isometric strength of knee extensors and, for this reason, can be used for practical, clinical, and research purposes.